Instillation of Prayer Values in Nature Shaping Students' Personalities - Nuryana, Ari; Suhartini, Andewi; Basri, Hasan (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2022)
Efforts made by educators in shaping the personality of good students have been carried out but have not produced maximum results. This study aims to identify the cultivation of prayer values This research uses a qualitative approach with a case study method. The results of the study show that: 1) the values of prayer that are instilled are religious values, such as being obedient to worship & loving cleanliness. Moral values, such as honesty, discipline, responsibility are not arrogant & polite. Social values, such as empathy & tolerance; 2) the process of inculcating the values of prayer is carried out in three stages, namely value transformation through PAI learning in class, value transactions through material appreciation & trans internalization of values through habituation programs; 3) the material used is PAI material related to fiqh; 4) the methods used are habituation of prayer, habituation of recitations of the Qur'an, habituation of Asmaul Husna, habituation of greeting in the morning, habituation of GPS & honesty stalls; 5) evaluation is carried out on the achievement of student personality using attitude assessment which results in prayer worship can shape the student's personality; 6) supporting factors for inculcating the values of prayer, namely the existence of worship facilities, school policies and partnerships with parents. While the inhibiting factors are less supervision from parents & a less supportive living environment.Ikthiar yang dilakukan oleh pendidik dalam membentuk kepribadian siswa yang baik telah dilakukan akan tetapi belum membuahkan hasil yang maksimal.Penelitian ini bertujuan untuk mengidentifikasi penanaman nilai-nilai sholat . Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Hasil penelitian menunjukkan bahwa 1) nilai-nilai ibadah shalat yang ditanamkan yaitu nilai religius, seperti taat beribadah & cinta kebersihan. Nilai moral, seperti jujur, disiplin, tanggungjawab, tidak sombong & sopan santun. Nilai sosial, seperti empati & toleransi; 2) proses penanaman nilai-nilai ibadah shalat dilakukan melalui tiga tahap, yaitu tranformasi nilai melalui pembelajaran PAI di kelas, transaksi nilai melalui penghayatan materi & trans internalisasi nilai melalui program pembiasaan; 3) materi yang dipakai adalah materi PAI yang berkaitan dengan fikih; 4) metode yang digunakan yaitu pembiasaan shalat, pembiasaan tilawah al-Qur’an, pembiasaan asmaul husna, pembiasaan sapa pagi, pembiasaan GPS & warung kejujuran; 5) evaluasi dilakukan pada hasil capaian kepribadian siswa menggunakan penilaian sikap yang hasilnya ibadah shalat dapat membentuk kepribadian siswa; 6) faktor pendukung penanaman nilai-nilai ibadah shalat yaitu adanya sarana ibadah, kebijakan sekolah dan kemitraan dengan orangtua. Sedangkan faktor penghambatnya yaitu pengawasan yang kurang dari orangtua & lingkungan tempat tinggal yang kurang mendukung.